Magnesium oxide supported nano-gold: a highly active catalyst for solvent-free oxidation of benzyl alcohol to benzaldehyde by TBHP - Choudhary, Vasant R.; Dumbre, Deepa K. (Catalysis Communications, 2009)
Nano-size gold particles deposited on MgO by the homogeneous deposition- precipitation showed very high catalytic activity with nearly 100% conversion of benzyl alcohol in a short reaction period (0.5 h) and more over showed excellent reusability in the process. Influence of the catalyst support (MgO, CaO, BaO, SrO, Al(2)O(3), Ga(2)O(3) and In(2)O(3)), method of gold deposition, Au loading and catalyst calcination temperature and also that of the reaction conditions (viz. reaction time and temperature) on the benzyl alcohol to benzaldehyde oxidation have been thoroughly investigated. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Alkaline earth oxides; Benzaldehyde; Benzyl alcohol; Gr.IIIa metal oxides; Oxidation

Mesoporous, ligand free Cu-Fe solid catalyst mediated CS cross coupling of thiols with aryl halides - Dumbre, Deepa K.; Selvakannan, P. R.; Patil, S. K.; Choudhary, Vasant R.; Bhargava, Suresh Kumar (Applied Catalysis A-General, 2014)
Solid catalyst derived from Cu-Fe hydrotalcite was demonstrated to be a novel, ligandless, efficient and environmentally greener catalyst for the synthesis of diaryl sulfurs from the C-S cross coupling reaction of substituted thiols with different aryl halides. This catalyst has shown higher product yield in the presence of dimethylformamide (as a solvent) and K2CO3 (as a base) at 120 C. Influence of different solvents and bases on the product yield has also been investigated. The catalyst can be easily separated from the reaction mixture, simply by filtration and reused several times without a significant loss of its activity. The catalyst has been fully characterized for its surface and bulk properties and the mesoporous CuO:Fe2O3 phase was attributed for its catalytic activity towards S-arylation reactions. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: C-S cross coupling; Cu-Fe-hydrotalcite; S-arylation